Project EX-India: A classroom-based tobacco use prevention and cessation intervention program. (February 2016) - Sidhu, Anupreet Kaur; Sussman, Steve; Tewari, Abha; Bassi, Shalini; Arora, Monika
Abstract: Tobacco use experimentation is most frequent between the ages of 15–24 in India. Therefore, programming to counteract tobacco use among adolescents is needed. There is a lack of evidence-based teen tobacco use prevention and cessation programs. The current study provides an outcome evaluation of the Project EX tobacco use prevention and cessation program among Indian adolescents (16–18 years). An eight-session classroom-based curriculum was adapted to the Indian context and translated from English to Hindi (local language). Next, it was tested using a quasi-experimental design with 624 Indian students at baseline, involving two program and two control schools, with a three-month post-program follow-up. Project EX involves motivation-enhancement (e.g., talk shows and games) and coping skills (e.g., complementary and alternative medicine) components. Program participants rated complementary and alternative medicine (CAM) activities like meditation, yoga and healthy breathing higher than talk shows and games. Compared to the standard care control condition, the program condition revealed a prevention effect, but not a cessation effect. Implications for prevention/cessation programming among Indian teens are discussed. This study was approved by the Independent Ethics Committee, Mumbai. Highlights: Outcome evaluation of school based tobacco control program  Project EX in India Quasi-experimental two-condition study design (program, standard care control) Four schools, two in each condition, conditions comparable at baseline Program condition revealed a significant prevention effect among adolescents Alternative medicine components were rated more favorably than other activities